CONFLICT OF LAW ASPECTS OF SAME-SEX PARTNERSHIP CONCLUDED ABROAD: SOME REMARKS FROM THE ASPECT OF DOMESTIC PRIVATE INTERNATIONAL LAW - Pavlović, Mina (Pravni zapisi, 2022)
Registered partnership is not regulated in the Serbian legal system, nor are there special conflict of law rules for this institute in the Law on resolving conflict of laws with regulations of other countries (the Serbian PIL Act). Therefore a question of conflict of law treatment of foreign registered partnership in the Serbian private international law is raised. In order to discover adequate conflict of law rule for determination of applicable law for the termination, personal and property effects of this relationship, the author examines if it is possible to do that through qualification or through creation of a new conflict of law rule in accordance with Article 2 of the PIL Act, which regulates filling the legal gaps. The author also points out to some conflict of law aspect of same-sex relationship (registered partnership) in cases with foreign element, if it is legalized in the Serbian legal system.